Design and implementation of an integrating modulated light camera - Light, Roger (2008)
In optical experiments, replacing the usual constant intensity light source with one that has its intensity modulated at a fixed frequency gives a number of advantages, namely moving the signal of interest away from low frequency noise, allowing the signal to be detected even in the presence of background illumination, as well as being able to gain more information about the experiment by measuring any change in the phase of the modulation.